Shear strengthening of full-scale RC T-beams using textile-reinforced mortar and textile-based anchors - Tetta, Zoi C.; Koutas, Lampros N.; Bournas, Dionysios A. (Composites. Part B, Engineering, 2016)
This paper presents a study on the effectiveness of TRM jacketing in shear strengthening of full-scale reinforced concrete (RC) T-beams focussing on the behaviour of a novel end-anchorage system comprising textile-based anchors. The parameters examined in this study include: (a) the use of textile-based anchors as end-anchorage system of TRM U-jackets; (b) the number of TRM layers; (c) the textile properties (material, geometry); and (d) the strengthening system, namely textile-reinforced mortar (TRM) jacketing and fibre-reinforced polymer (FRP) jacketing for the case without anchors. In total, 11 full-scale RC T-beams were constructed and tested as simply supported in three-point bending. The results showed that: (a) The use of textile-based anchors increases dramatically the effectiveness of TRM U-jackets; (b) increasing the number of layers in non-anchored jackets results in an almost proportional increase of the shear capacity, whereas the failure mode is altered; (c) the use of different textile geometries with the same reinforcement ratio in non-anchored jackets result in practically equal capacity increase; (d) TRM jackets can be as effective as FRP jackets in increasing the shear capacity of full-scale RC T-beams. Finally, a simple design model is proposed to calculate the contribution of anchored TRM jackets to the shear capacity of RC T-beams.